2020
DOI: 10.1109/access.2020.2972644
|View full text |Cite
|
Sign up to set email alerts
|

ALTRA: Cross-Project Software Defect Prediction via Active Learning and Tradaboost

Abstract: Cross-project defect prediction (CPDP) methods can be used when the target project is a new project or lacks enough labeled program modules. In these new target projects, we can easily extract and then measure these modules with software measurement tools. However, labeling these program modules is time-consuming, error-prone and requires professional domain knowledge. Moreover, directly using labeled modules in the other projects (i.e., the source projects) can not achieve satisfactory performance due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Random Forest is an integrated learning pattern recognition method [ 19 , 38 ]. It has been demonstrated that Random Forest has good performance in CPDP [ 27 , 39 , 40 ] due to its high tolerance to outliers and noise. Random Forest is also less prone to fitting characteristics [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Random Forest is an integrated learning pattern recognition method [ 19 , 38 ]. It has been demonstrated that Random Forest has good performance in CPDP [ 27 , 39 , 40 ] due to its high tolerance to outliers and noise. Random Forest is also less prone to fitting characteristics [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yuan et al [ 27 ] used TrAdaBoost to determine weights for samples based on Burak filter and used weighted support vector machines to build the model to improve the CPDP model. Chao et al [ 28 ] proposed a two-phase CPDP method called TPTL, using a source project estimator to select source projects with similar data distribution as the target project and using two improved TCA + to construct models for prediction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their study EMBLEM improved P opt 20 and G-scores performance. Yuan et al [8] worked on data labeling in cross-project defect prediction. The proposed method is called ALTRA which uses active learning and TrAdaBoost (Transfer learning Adaboost).…”
Section: Previous Work 21 Just-in-time Software Defect Predictionmentioning
confidence: 99%
“…Zhu et al [7] proposed a method named CooBA based on adversarial transfer learning, which obtains information from cross-project bug reports and focuses only on common features across projects, and CooBA incorporates adversarial learning to ensure that the common information can be extracted effectively. Yuan et al [8] presented an active learning and tradaboost (ALTRA) method. It firstly selects some instances from the source project, which have the most similar distributions to that of the target project, and uses a iterative way in the target instances until the specific number of instances are selected.…”
Section: Introductionmentioning
confidence: 99%